Performing the sacred: Christian representation and the arts - Bino, Carla M.; Ricasoli, Corinna (Studies in religion and the arts, 2023)
"What does 'performance' mean in Christian culture? How is it connected to rituals, dramatic and visual arts, and the written word? Performing the Sacred: Christian Representation and the Arts explores both the meaning of re-presentation and the role of performance within the Christian tradition between arts and drama. The essays in this book demonstrate that the idea of performance was central to Christian theology and that-from the Middle Ages to the Early Modern era-it became a device through which people saw, prayed, preached, wrote, imagined, officiated rites, celebrated cults, and practiced devotions. Seen that performance is a habitus within Christianity, performing the sacred does not just mean representing it, but rather enacting it in a tangible, visible and involved way"--